Peran Media Sosial terhadap Perilaku Peserta Didik di Era Globalisasi - Khafifatu Syahraini; Askari Zakariah1; Novita Novita (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
Rapid technological advances have made human life easier, especially in terms of communication. This study uses a descriptive literature study method to explore the role of adab as a foundation in Islamic education and the impact of social media on education in the digital era. Social media, such as Facebook, Twitter, and Instagram, have become an integral part of modern life and education. These platforms allow students to develop technical and social skills, expand their network of friends, and facilitate social interaction and learning motivation. Social media also provides the infrastructure for creating and delivering learning content. However, unwise use of social media can disrupt time management, increase the risk of cyberbullying, and affect self-image. This study shows that social media has great potential in supporting student education and development, but also has negative impacts that need to be managed. To maximize benefits and minimize negative impacts, digital literacy, guidance, and supervision from teachers and parents, as well as clear usage policies are needed. With the right approach, social media can be an effective tool to improve students' learning and social skills in the era of globalization.